The Relationship Between the Constitutional Judges’ Selection by the House of Representatives and The Position of Judges in Judicial Review Decisions - Muchamad Ali Safa’at; Aan Eko Widiarto; Haru Permadi; Muhammad Dahlan (Constitutional Review, 2024)
The two issues raised in this study are the selection mechanism for constitutional judges nominated by the House of Representative (DPR) and the correlation between the selection of constitutional judges nominated by the DPR and the position of the judge in the decision to review the law. This research analizes the position of the constitutional judges on 8 judicial review decision which correlated to the authority and interests of the DPR. Judges who are nominated through a highly transparent and participatory selection process or a transparent and participatory process may rule in favor of or against the interests of the DPR. However, judges who are nominated through a selection process that is not transparent and participatory will all make decisions in favor of the interests of the DPR. That finding show that the judge nominated through a highly transparent and participatory selection process tends to be more independent than the judge nominated through less transparent and participatory selection process.